Significant association between insulin-like growth factor 2 mRNA-binding protein 2, interleukin-6 polymorphisms, and type 2 diabetes mellitus - Elmutuz H Elssaig; Eltayib H Ahmed-Abakur; Tarig M S Alnour; Mohamed A. Alsubai; Aadil Yousif (Journal of Research in Medical Sciences)
Background: The study aimed to detect the association between insulin-like growth factor 2 mRNA-binding protein 2 (IGF2BP2) and interleukin-6 (IL-6) polymorphisms among type 2 diabetes mellitus (T2DM). Materials and Methods: This study involved 500 individuals; 250 obese DM cases and 250 healthy controls. The polymerase chain reaction restriction fragment length polymorphism was used to identify the genotype of the IGF2BP2 gene for the small nucleoproteins rs4402960 (G>T) and small nucleoproteins rs800795 (G>C). Results: The results indicated that the mutant C-allele of the single nucleotide polymorphism (SNP) rs1800795 variant was highly significantly associated with the study group (P = 0.002). The occurrence of genotypes (C/G and C/C) versus normal G/G genotype of the IL-6 variant was highly significant (P = 0.004) in the study group (49.2% vs. 50.8%) compared to the control group (62% vs. 38%). Similar findings were observed in SNPs for the rs440960 variant, in which the T-allele indicated a highly significant relationship (P = 0.0001) with the study group; the frequency of G/G genotype versus both (T/T and G/T) genotypes was highly significant (P = 0.0001) in the case group (34% vs. 66%) than in the healthy control group (52% vs. 48%). Conclusion: The current study indicated that IGF2BP2 rs4402960 and IL-6 rs1800795 polymorphism were highly significantly associated with the increased risk of obese T2DM among the Saudi Arabian population and presented a genetic model to screen the high-risk individuals with further validations.